The Study of Feedback in Writing from College English Teachers and Artificial Intelligence Platform Based on Mixed Method Teaching. - Liu, Houtao; Ma , Wenjia; Wu, Tingting; Xin, Chuanhua (Pacific International Journal, 2022)
Abstract:With the development of modern teaching technology, intelligent writing correction platform has emerged and become an effective way to supplement traditional feedback from teachers under the new situation. The main theoretical basis of this study is dynamic evaluation theory. The experimental group and the controlled group were assigned three writing tasks. The statistical analysis software SPSS was used to analyze the data results. In the study, literature review, experiment, questionnaire and interview methods were used. The literature summarizes the development status of teacher feedback and intelligent platform correction at home and abroad. The experimental method is to compare the similarities and differences between teacher feedback and intelligent platform correction in specific experiments. Through questionnaires and interviews, we can understand the attitudes of teachers and students towards the intelligent correction platform. The research results show that the two feedback methods are consistent and have obvious differences. Teacher feedback has more significant advantages in the two dimensions of text structure and content, while the intelligent writing correction platform is too general and procedural in the feedback of these two dimensions. In comparison, the feedback of the intelligent writing correction platform on vocabulary and grammar is more detailed, giving students detailed information. The combination of the two ways of feedback and the application of them to the teaching of English writing in senior high schools will have a more ideal effect, which will have a positive effect on the improvement of senior high school students' English writing level. Keywords: Dynamic evaluation theory; Teacher feedback; Feedback from AI writing platform; contrastive study